Sulfobutylether-β-cyclodextrin: A functional biopolymer for drug delivery applications. (1st February 2023) - Pardeshi, Chandrakantsing V.; Kothawade, Rucha V.; Markad, Ashwini R.; Pardeshi, Sagar R.; Kulkarni, Abhijeet D.; Chaudhari, Prashant J.; Longhi, Marcela R.; Dhas, Namdev; Naik, Jitendra B.; Surana, Sanjay J.; García, Mónica C.
Abstract: Sulfobutylether β-cyclodextrin (SBE-β-CD) is a polyanionic cyclic oligosaccharide that contains glucopyranose units forming a torus ring-like structure. SBE-β-CD is gifted with many favorable properties viz. relatively high solubility (>50 folds compared to β-CD), improved stability, and biocompatibility that praised SBE-β-CD as a smart polymer for drug delivery applications. Commercially, SBE-β-CD is popular by its brand name Captisol®. The present review discusses the structure, properties, and preparation methods of SBE-β-CD-based inclusion complexes (ICs). Furthermore, we discuss here the preparation and applications of SBE-β-CD ICs-based nanoparticulate drug delivery systems, which combines the merits of both, ICs (enhanced solubility) and nanoparticles (NPs, targeted therapy). Patents on and FDA-approved Captisol®-enabled products are tabulated in the benefit of readers. The toxicological aspects and current clinical status of SBE-β-CD or SBE-β-CD-based products are briefly explained in the present review. In our opinion, the present review would be a pathfinder to allow dissemination of information on SBE-β-CD. Graphical abstract: Unlabelled Image Highlights: Sulfobutylether-β-cyclodextrin (SBE-β-CD) is a polyanionic cyclic oligosaccharide. SBE-β-CD is used to improve the solubility, and stability of small molecules. It lessens the volatility, irritation, and hides smell or taste of small molecules. Present review is the state-of-the-art collection on SBE-β-CD. SBE-β-CD is an emerging functional biopolymer for drug delivery.